Density‐Dependent Effects on the Reproductive Ecology of Trees in a Temperate Woodland - Eleanor E. Jackson; Matthew P. Greenwell; James M. Bullock; Tom H. Oliver; Susie Topple; Christopher W. Foster; Sofia Gripenberg (Ecology and Evolution)
ABSTRACT The reproductive success of plants often depends on their local conspecific densities. The degree of isolation from conspecific plants can mediate an individual's interactions with other organisms. For example, a high density of flowers can attract pollinators and improve seed set, and a high density of seeds can attract enemies such as seed predators. It is the joint outcome of positive and negative density‐dependent effects that will determine the spatial distribution of a population, yet they are rarely studied simultaneously. We related two indicators of reproductive success (fruit set and fruit drop) to tree size and the density of neighbouring conspecifics for 32 Crataegus monogyna (Rosaceae) individuals in a temperate woodland. Overall, 26% of flowers set seed, but seed set was not density dependent. We found that 25% of fruits were dropped before reaching maturity, and 24% of mature fruits were dropped before the typical dispersal period. The drop of both immature and mature fruits increased with the density of reproductive conspecifics in this system, with potential implications for spatial patterns of seedling recruitment.